The Impact of Migration on Optimism and Subjective Well-Being: Evidence from the Indonesian Family Life Survey - Alabshar, Nufi; Giyarsih, Sri Rum; Pitoyo, Agus Joko (Journal of Population and Social Studies [JPSS], 2023)
When migrating, a person will expect better well-being than they had in their area of origin. Much research only focuses on how migration affects objective well-being, even though subjective well-being describes well-being more than an economic perspective. This study aims to investigate the impact of migration on the optimism and subjective well-being of migrants. Migration is considered when it crosses district or city boundaries, whether internal or international. The method used in this study is the difference-in-differences (DID) method, which allows us to determine the impact of migration. Using panel data from the Indonesian Family Life Survey (IFLS) in 2007 and 2014, the results show that migration has a positive effect on optimism, economic opinion, personal and household needs opinion, children’s needs opinion, and happiness of migrants. Migration does not have a significant impact on happiness despite a positive correlation towards it. Other control variables, such as urban regional classification, younger age, male gender, married status, and higher education, positively affect subjective well-being.